Ultrasound-Guided Biopsies: Medium and Large Joints - Polido-Pereira, Joaquim (Frontiers in Medicine, 2019)
Ultrasound-guided needle synovial biopsies are useful for clinical practice and research in rheumatology. With the emergence of personalized medicine for the treatment of inflammatory rheumatic diseases, it is predicted that this technique will be increasingly used in the near future. Standardized characterization of the technical aspects of ultrasound-guided needle synovial biopsies is needed in order to produce solid evidence on the safety and effectiveness of the technique.